Distinguishing the virtuous city of Alfarabi from that of Plato in light of his unique historical context - Ali, Ishraq (HTS teologiese studies, 2019)
There is a tendency among scholars to identify Alfarabi’s political philosophy in general and his theory of the state in particular with that of Plato’s The Republic. Undoubtedly Alfarabi was well versed in the philosophy of Plato and was greatly influenced by it. He borrows the Platonic concept of the philosopher king and uses it in his theory of the state. However, we argue that the identification of Alfarabi’s virtuous city with that of Plato’s The Republic is an inaccurate assessment as it involves overlooking Alfarabi’s unique religiopolitical context. Alfarabi was a Muslim political philosopher, and the present article intends to understand Alfarabi’s theory of the state in light of his historical context. The article shows that, viewed through the prism of Islamic religion and political history, Alfarabi’s virtuous city seems distinct from that of Plato’s The Republic.